Cancer of the Testis - Laguna, M. Pilar; Albers, Peter; Richie, Jerome P.; Bokemeyer, Carsten; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2011)
Cancer of the Testis presents a thorough account of every aspect of this disease, including histology, risk factors, prognosis, clinical presentation, diagnosis and treatment. Additionally, there is a focus on the pertinent issues of fertility, late effects of primary therapy, follow-up after primary treatment and testicular cancer in childhood. With an international authorship comprised of many of the key contributors to the field, this book brings together a rich and balanced range of perspectives. A state-of-the-art reference volume on testicular cancer, this book is essential reading for urologists, medical oncologists and radio-oncologists. M. Pilar Laguna, MD PhD, is an Associate Professor in Urology at the University of Amsterdam, The Netherlands. Peter Albers, MD, is Chairman of the Department of Urology at Dusseldorf University, Germany. Carsten Bokemeyer, MD, is Director of Oncology and Hematology at Hubertus Wald Tumorzentrum at the University Medical Center in Hamburg, Germany. Jerome P. Richie, MD, is the Elliot C. Cutler Professor of Urologic Surgery at Harvard Medical School and Chief of Urology at Brigham and Women’s Hospital in Boston, USA.
Histological Classification and Pathology of Testicular Tumors -- Risk Factors and Genetical Characterization -- Primary Non-Germ Cell Tumors of the Testis -- Staging and Prognostic Systems -- Testicular Tumor Markers -- Radical Orchiectomy and Testis Sparing Procedures for the Management of Germ Cell Tumors -- CIS and Bilateral Cancer: Clinical Presentations and Diagnostics -- Diagnostic and Therapeutic Laparoscopic Retroperitoneal Lymph Node Dissection: The American View -- Laparoscopic Retroperitoneal Lymph Node Dissection for Stage I and II: The European View -- Radiographic Diagnosis and Staging -- Treatment of Non-Seminoma: Stage I -- Treatment of Patients with Stage II A/B and Advanced Nonseminomatous Germ Cell Tumors -- Treatment of Seminoma: Stage I -- Stage II Seminoma and Advanced Disease -- Treatment of Relapse -- Post-Chemotherapy Retroperitoneal Lymph Node Dissection -- Surgical Resection at Other Sites -- Extra Gonadal Germ Cell Tumors -- New Systemic Therapies for Refractory Tumors -- Management of Late Relapse -- Testicular Cancer: Late Effects of Treatment -- Fertility Issues -- Follow-Up after Primary Treatment -- Testicular Cancer in Childhood.
Keywords: Urology; Oncology .; Radiology; Urology; Oncology; Imaging / Radiology